Feminisme Pasca-Kolonial: Menafsirkan Ulang Teks Keagamaan untuk Keadilan Gender Global - Ahmad Ahmad; Naharuddin SR; Muhammad Said; Minhajuddin Madi; Faisal Nur Shadiq Shabri (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2025)
In the era of globalization, gender inequality continues to persist within religious traditions, often reinforced by patriarchal interpretations shaped by colonial legacies that hinder women’s rights and broader efforts toward global justice. This paper explores how postcolonial feminism can reinterpret religious texts to challenge these norms and promote equitable gender relations. Using a qualitative interpretive design within a descriptive-comparative framework, the study analyzes key texts from the Qur’an, the Bible, and the Vedas through contextual exegesis, etymological analysis, and dialogical engagement with participants from South Asia, Sub-Saharan Africa, and the Middle East. The findings reveal that traditional patriarchal readings stem from socio-historical contexts rather than inherent textual mandates, with colonial influences intensifying hierarchical structures. Postcolonial feminist reinterpretations uncover egalitarian potentials, including shared responsibility in Qur’anic verses, ontological equality in Biblical creation narratives, and gender balance in Vedic symbolism. The study extends postcolonial feminist theory by integrating decolonial hermeneutics into scriptural analysis, offering a framework for reimagining gender agency within sacred texts. Practical strategies, such as workshops that empower marginalized voices, demonstrate a shift toward inclusive discourse, providing pathways for policy reform and community transformation in pursuit of gender justice.